In Vitro Effect Of Insecticide Emamectin Benzoate On Earth Worm, Metaphire Posthuma, Using Contact Filter Paper Method (Applied Biological Research, 2019)
Pesticides are extensively used across the globe to combat pests for higher crop production (Kohler  and Triebskorn, 2013). In modern farming the use of intensive agriculture practices is mostly  criticized as it adversely affects the environmental health, contaminate soil and reduces biodiversity  (Datta et al., 2016). More than 99.7% pesticides used in agriculture are persistent and accumulate in  surrounding environment (Tejada et al., 2017). Pesticides adversely affect soil organisms including  earthworm (Maboeta et al., 2004). Earthworms, the major biomass of soil macrofauna, are highly  susceptible to chemicals so are considered as pollution-indicator soil organism (Jouquet et al., 2010). The ingestion of soil minerals and organic material by earthworm facilitates humification  and mineralization of soil nutrients. The pesticide residues in soil cease the physiological function  and ecological structure of earthworms and cause their mortality (Maboeta et al., 2004) as well as  damage higher trophic levels (Van Gestel et al., 2011). Since earthworm is a significant route for  the uptake of soil contaminants, therefore toxicity study on earthworms may help in understanding  the mechanism by which these pesticides affect the soil quality, especially soil biota. Emamectin benzoate is a semisynthetic bioinsecticide composed of naturally occurring compound, avermectin,  extracted from Streptomyces avermitilis. Emamectin benzoate is used to control lepidopteron  insects in vegetables, cotton and tobacco. Emamectin benzoate is a chloride channel activator that  prevents muscle contraction, induces cessation of feeding and finally causes the death of pests. Earlier the toxic effects of antibiotics on earthworm have been demonstrated in many studies (Gunn  and Sadd, 1994; Diao et al., 2007). However, the chemical used in present study has been studied  for the first time under Kumaun (Uttarakhand) agroclimatic conditions.
Keywords: Insecticide; Emamectin Benzoate; Metaphire Posthuma; Earth Worm